Effects of chronic hypoxia on the gene expression profile in the embryonic heart in three Chinese indigenous chicken breeds (Gallus gallus) - Li, Xiaofeng; Abdel-Moneim, Abdel-Moneim Eid; Hu, Zhongze; Mesalam, Noura M.; Yang, Bing (Frontiers in Veterinary Science, 2022)
Hypoxia exposure (HE) has adverse impacts on the embryonic development of chicken, whereas the mechanism underlying the response of the heart to HE during embryo development in birds is still unclear. Therefore, our study was designed to reveal the hub genes and the signaling pathways linked to chronic hypoxia stress. Thus, the gene expression microarray GSE12675, downloaded from the GEO database, included 12 embryonic heart samples in hypoxia and normoxia of three Chinese indigenous chicken breeds [Shouguang (SG), Tibetan (TB), and Dwarf Recessive White (DRW) chickens]. A total of 653 to 714 breed-specific differentially expressed genes (DEGs) were detected in each pairwise comparison. Gene ontology (GO) showed that the DEGs were mainly involved in biological processes, including vasoconstriction, cell differentiation, and the positive regulation of vasoconstriction. KEGG enrichment revealed that the DEGs were mainly enriched in MAPK, PPAR, insulin, adrenergic signaling in cardiomyocytes, etc. Moreover, 48 genes (e.g., SGCD, DHRS9, HELQ, MCMDC2, and ESCO2) might contribute to the response of the heart to HE. Taken together, the current study provides important clues for understanding the molecular mechanism of the heart's response to HE during the embryonic period of chicken.